Prolonged mechanical ventilation and chronic critical illness - Bugedo, Guillermo; Egal, Mohamud; Bakker, Jan (Journal of Thoracic Disease; Vol 8, No 5 (May 01, 2016): Journal of Thoracic Disease, 2016)
Intensive care medicine has grown effectively in recent decades, parallel to multiple scientific and technological advances of our society. However, patients who survive the initial insult may have significant functional dependency, with slow recovery and high mortality rates (1-3).